A Review: Adsorption and Removal of Heavy Metals Based on Polyamide-amines Composites - Wang, Qian; Zhu, Sining; Xi, Chen; Zhang, Fan (Frontiers in Chemistry, 2022)
In recent years, the problem of heavy metal pollution has become increasingly prominent, so it is urgent to develop new heavy metal adsorption materials. Compared with many adsorbents, the polyamide-amine dendrimers (PAMAMs) have attracted extensive attention of researchers due to its advantages of macro-molecular cavity, abundant surface functional groups, non-toxicity, high efficiency and easy modification. But in fact, it is not very suitable as an adsorbent because of its solubility and difficulty in separation, which also limits its application in environmental remediation. Therefore, in order to make up for the shortcomings of this material to a certain extent, the synthesis and development of polymer composite materials based on PAMAMs are increasingly prominent in the direction of solving heavy metal pollution. In this paper, the application of composites based on PAMAMs and inorganic or organic components in the adsorption of heavy metal ions is reviewed. Finally, the prospects and challenges of PAMAMs composites for removal of heavy metal ions in water environment are discussed.